CREDIT RISK MANAGEMENT OF MFIS FOUND IN ETHIOPIA - Ahmed, Amina; Seyoum, Arega; Kedir, Hamdu; Kedir, Saniya (European Scientific Journal, ESJ, 2015)
This study is conducted to assess the credit risk management of MFIs found in Ethiopia and to rate these institutions according to their rank. In conducting this study secondary data from audited annual reports of the MFIs, performance analysis report bulletins, the web sites of the MFIs and from the Mix Market (MIX) was collected. The Morgan Stanley approach was employed to assess the credit risk management of the MFIs rated in accordance to their grade. Accordingly the overall credit risk management of these MFIs is ranked as follows ACSI (1st), DECSI (2nd), Wasasa (3rd ), PEACE, OCSSCO,and BUSSA (4th ), ADCSI (5th ), SFPI(6th ),OMO(7th ),and Wisdom (8th). Based on their result these institutions are recommended to re-assess their credit risk management process and procedures in each rating factors in which they fail to achieve the best grade in the Morgan Stanley grading approach.